Research on hybrid modified pathfinder algorithm for optimal reactive power dispatch - Suresh, V.; Senthil Kumar, S. (Bulletin of the Polish Academy of Sciences Technical Sciences, 2021)
Hybridization of meta-heuristic algorithms plays a major role in the optimization problem. In this paper, a new hybrid meta-heuristic algorithm called hybrid pathfinder algorithm (HPFA) is proposed to solve the optimal reactive power dispatch (ORPD) problem. The superiority of the Differential Evolution (DE) algorithm is the fast convergence speed, a mutation operator in the DE algorithm incorporates into the pathfinder algorithm (PFA). The main objective of this research is to minimize the real power losses and subject to equality and inequality constraints. The HPFA is used to find optimal control variables such as generator voltage magnitude, transformer tap settings and capacitor banks. The proposed HPFA is implemented through several simulation cases on the IEEE 118-bus system and IEEE 300-bus power system. Results show the superiority of the proposed algorithm with good quality of optimal solutions over existing optimization techniques, and hence confirm its potential to solve the ORPD problem.
Keywords: optimal reactive power dispatch (ORPD); real power losses; pathfinder algorithm (PFA); modified pathfinder algorithm (mPFA); hybrid pathfinder algorithm (HPFA)